Identification of Individual Zebrafish (Danio rerio): A Refined Protocol for VIE Tagging Whilst Considering Animal Welfare and the Principles of the 3Rs - Rácz Anita; Allan Brooke; Dwyer Toni; Thambithurai Davide; Crespel Amélie; Killen Shaun S. (MDPI, 2025)
Simple SummaryIn aquatic ecology research studies commonly employ a tagging technique named visible implant elastomer (VIE). Despite existing widespread guidance on the use of this marking technique on fish, there is still a lack of information regarding efficiency in small fishes, as well as its impact on fish welfare. The current paper highlights important animal welfare issues and introduces a newly improved VIE tagging protocol, presenting information on individual survival rate, tag retention, and use of different elastomer colours, quantified in different populations and age groups of zebrafish. Specifically, we compare a previously used tagging method with a newly improved protocol which places particular emphasis to the Three Rs, helping to refine this scientific procedure. The shared detailed protocol and information will be beneficial to the zebrafish research community and beyond.In aquatic ecology, studies have commonly employed a tagging technique known as visible implant elastomer (VIE). This method has not been widely adopted by the zebrafish research community and also lacks refinement with regard to animal welfare. The current paper introduces a new VIE tagging protocol, with the aim of improving existing tagging techniques by placing particular emphasis on the Three Rs. To improve animal welfare and fish survival, we added the use of an analgesic compound (lidocaine) through the marking procedure, followed by after-treatment with antiseptics (melaleuca, aloe vera, and PVP-I as active ingredients) to improve tissue regeneration and healing. The newly improved protocol has been quantitatively evaluated on different populations and age groups of zebrafish. This study will be useful to the scientific zebrafish community and to the wider field including biologist and aquarists, especially in consideration of animal welfare, where tagging techniques are considered as a potential noxious stimulus for fish.